#Eduresistance: a critical analysis of the role of digital media in collective struggles for public education in the USA. (1st January 2018) - Thapliyal, Nisha
ABSTRACT: From Facebook-coordinated high-school walkouts to compelling Internet-based protest art that has accompanied recent teacher strikes, grassroots education activism in the USA has gone digital. Despite the proliferation of research on the mediatisation of education policy, few studies have explored the ways in which activists for public education engage with Web 2.0 technologies. This paper makes a contribution to this under-researched area by exploring selected activist accounts including Parents Across America, United Opt Out National, and the PS 2013 campaign in New York City. I draw on critical, feminist, and cultural studies theories of education and social movement media to analyse activist media practices in a policy and political milieu dominated by corporate media and neoliberal governance structures. The analysis reveals that progressive education activists strategically deploy digital media to amplify voice, build collective identity, and disseminate alternative knowledge to enable direct action. A situated analysis also reveals significant differences in activist media practice which are shaped by particular political histories and geographies. The paper concludes with a discussion about future lines of inquiry into the role of digital media in collective struggles for public education.